Taṭwīr Adawāt al-Taqwīm al-Takwīnī al-Qā’imah ʿalā Kahoot li-Tarqīyat Itqān al-Mufradāt fī Taʿlīm al-Lughah al-ʿArabīyah bil-Madrasah al-Mihanīyah - Nur, Aqida Miladia; Mudrofin, Mudrofin; Bukhori, Nada Fithria (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2023)
This study aims to develop and test the effectiveness of formative assessment tools based on Kahoot to improve students' mastery of Arabic vocabulary. This study responds to the lack of variety in traditional assessment methods, which makes students feel bored and negatively impacts their ability to understand and retain vocabulary. The study used the Research and Development (RD) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The study involved a sample of students divided into experimental and control groups, and the test results were analyzed using appropriate statistical analysis. The findings showed that interactive assessment tools based on Kahoot effectively enhance students' mastery of Arabic vocabulary, with a statistically significant difference in test results between the groups, where the experimental group demonstrated a noticeable improvement in test scores.